2022
DOI: 10.1200/po.22.00246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Practice Gaps on the Implementation of Personalized Medicine in Advanced Non–Small-Cell Lung Cancer

Abstract: PURPOSE Personalized medicine presents new opportunities for patients with cancer. However, many patients do not receive the most effective personalized treatments because of challenges associated with integrating predictive biomarker testing into clinical care. Patients are lost at various steps along the precision oncology pathway because of operational inefficiencies, limited understanding of biomarker strategies, inappropriate testing result usage, and access barriers. We examine the impact of various clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…Potential solutions in our study were geared towards crafting a framework that promotes successful molecular testing, including strategies to increase the yield of the biopsy procedure itself, which could be disseminated via workshops at specialty society meetings in addition to the literature. Biopsies should be performed using coaxial technique and target the periphery of large tumors to avoid central necrosis [31]. Review of pre-procedural imaging, such as fluorodeoxyglucose-PET and contrastenhanced CT, facilitates the identification of necrotic areas [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential solutions in our study were geared towards crafting a framework that promotes successful molecular testing, including strategies to increase the yield of the biopsy procedure itself, which could be disseminated via workshops at specialty society meetings in addition to the literature. Biopsies should be performed using coaxial technique and target the periphery of large tumors to avoid central necrosis [31]. Review of pre-procedural imaging, such as fluorodeoxyglucose-PET and contrastenhanced CT, facilitates the identification of necrotic areas [31].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies should be performed using coaxial technique and target the periphery of large tumors to avoid central necrosis [31]. Review of pre-procedural imaging, such as fluorodeoxyglucose-PET and contrastenhanced CT, facilitates the identification of necrotic areas [31]. The shorter procedure time afforded by realtime CT, often referred to as "CT fluoroscopy, " creates time for ROSE and the collection of additional samples [32].…”
Section: Discussionmentioning
confidence: 99%
“…5,10,19 Strategies that reduce the time required for tumor genotyping may improve adherence to testing guidelines and patient outcomes. 16,17 An ASCO taskforce survey of US oncologists found that 23% of the respondents agreed that delaying treatment while waiting for test results was always or often a reason to not order biomarker testing. 17 Most providers (98%) considered 1-2 weeks as the acceptable wait time for biomarker test results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these diagnostic methods are profoundly underutilized, primarily because of failures in biospecimen processing, testing, and result reporting. 16,17 Therefore, optimization of the diagnostic paradigm for tumor genotyping may improve the delivery of precision oncology treatments to patients with lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges such as insufficient or poor quality samples, and slow turnaround time [5], have further hindered broad adoption. For example, in a 2022 multisource database investigation, nearly 50% of patients were unable to benefit from precision medicines due to factors linked with obtaining biomarker results; 18% received inaccurate results due to test limitations or errors; and 4% started on a less precise treatment due to prolonged test turnaround time [6]. Therefore, there is an outstanding need for rapid, comprehensive, reliable, and low-cost methods that can identify patients as eligible for precision treatment and clinical trials.…”
Section: Introductionmentioning
confidence: 99%